Scripture in transition : essays on Septuagint, Hebrew Bible, and Dead Sea scrolls in honour of Raija Sollamo - Jokiranta, Jutta.; Sollamo, Raija.; Voitila, Anssi. (Supplements to the Journal for the Study of Judaism, 2008)
Altogether 46 essays in honour of Professor Raija Sollamo contribute to explore various aspects of the rich textual material around the turn of the era. At that time Scripture was not yet fixed; various writings and collections of writings were considered authoritative but their form was more or less in transition. The appearance of the first biblical translations are part of this transitional process. The Septuagint in particular provides us evidence and concrete examples of those textual traditions and interpretations that were in use in various communities. Furthermore, several biblical concepts, themes and writings were reinterpreted and actualised in the Dead Sea Scrolls, illuminating the transitions that took place in one faction of Judaism. The topics of the contributions are divided into five parts: Translation and Interpretation; Textual History; Hebrew and Greek Linguistics; Dead Sea Scrolls; Present-Day.